Curtis's Patent (1862)
Diagram represents the form and boundaries of 50 acres of land situated in the parish of St. Ann.
It comprises a part of 2 patents as shown above; the parcel containing 13 acres 1 rood and 16 perches forms a portion of a run of land known as Curtis's patent, the other and larger parcel containing 36 acres 2 roods and 24 perches forms a portion of a run of land named Gabriel Jones's patent. It is now in the possession of Edward Martin.
Estate Map
NLJCols20082021
Keywords: Gabriel Jones's patent; Curtis's Patent